Factors Affecting Good University Govermance: The Concept of Theoretical - Januri Januri, S.E., M.M., M.Si (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Factors Affecting Good University Govermance: The Concept of Theoretical